Utilization Of Website-Based Learning Videos For Mathematics Learning - Pratama, Singgih; Hendriana, Benny (Universitas Wiralodra, 2023)
This research has the aim of developing learning media in website-based mathematics lessons by using video as a material deliverer. Research and Development with a 4D model is used in this study in the process of developing mathematics learning media using the website. The interpretation, design, development, and distribution are the four main stages in the 4D model. There are 77 grade VII students of SMPN 11 Depok as the subjects of this research. Media expert validation is the source of the validity test in this study while the validity of media experts and student responses are the basis of the practicality test in this study so that the development of website-based media in this study is assessed as valid